PEMETAAN DAERAH PENCEMARAN ANTROPOGENIK BERBASIS SUSEPTIBILITAS MAGNETIK - Estevanus Kristian Huliselan (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
The applicability of environmental magnetism methods based on the study of magnetic susceptibility (Ï‡) have been successfully used over several decades to characterize and quantify the degree of anthropogenic pollution of different environmental systems. Moreover, in recent years, there have been a number of studies linking low frequency magnetic susceptibility (Ï‡LF) and heavy metal content in different kinds of material. Furthermore, the Ï‡LF technique can be used as a potential method to discriminate polluted and unpolluted samples. The plots of Ï‡LF versus frequency-dependent magnetic susceptibility (Ï‡FD) have been shown to be effective as discriminating tool for sources of magnetic minerals. The polluted and unpolluted samples display disparate distribution patterns of Ï‡LF and Ï‡FD. Furthermore, the pollution area can be roughly inferred. We conclude that measurement of Ï‡LF and Ï‡FD can serve as a convenient and effective method for detection of polluted and unpolluted areas. This method is promising as an alternative to conventional chemical analysis. Keywords: environmental magnetism, pollution area, anthropogenic, heavy metals, magnetic susceptibility.